Intraseasonal modulation of sea surface temperatures in the Tropical North Atlantic by African Easterly Waves - Marc Kakante Mendy; Florent Gasparin; Manon Gévaudan; Moussa Diakhaté; Issa Sakho; Julien Jouanno (Ocean Science, 2026)
The sea surface temperature (SST) variability in the Tropical North Atlantic (TNA) plays a crucial role in the regional climate by modulating the Intertropical Convergence Zone (ITCZ) and influencing precipitation, convective systems, and tropical cyclones. While atmospheric synoptic-scale intraseasonal variability in this region is dominated by African Easterly Waves (AEWs), their impact on SST remains poorly understood. This study investigates the modulation of SST by AEWs using a regional configuration of a coupled ocean-atmosphere model and moored surface buoy air-sea observations. The results reveal a significant AEWs signature in SST anomalies, with typical temperature fluctuations of approximately ±0.3 °C (reaching up to ±0.5 °C for the strongest events). A heat budget analysis shows that AEWs mainly influence SST through modulation of the latent heat flux, shortwave radiation, and vertical mixing. The contribution of ocean mixing and that of the air-sea fluxes appear to be of similar order. The dominant 3–5 d AEWs exhibit a stronger impact than their 6–9 d counterparts. These findings highlight the role of AEWs in driving SST variability and mixed-layer dynamics, underscore the importance of accurately representing them in coupled climate models, and call for further investigation into their influence on the mean and seasonal upper-ocean state.

Blue carbon stocks, accumulation rates and knowledge gaps in Africa - Janine B. Adams; Paula Pattrick; Pere Masqué; Dennis Adotey; Elsheikh Bashir Ali; Abdelgadir Bashir Mohamed Awatif; Mohamed Fathi Ben Hamouda; Moncef Benmansour; Joseph F. Charles; Jerome Harlay; Lucienne Human; Linet Kiteresi Imbayi; et al. (Ocean & Coastal Management, 2026)

Urban beach evolution in Saint Louis, Senegal (West Africa) using shore-based camera video monitoring as a management tool - Amadou Diouf; Cheikh Omar Tidjani Cissé; Rafael Almar; Baba Sy; Boubou Aldiouma Sy; Adelaide Taveneau; Issa Sakho; Bamol Ali Sow; Grégoire Abessolo Ondoa; Abdoulaye Ndour; Kader Ba; Erwin W.J. Bergsma; et al. (Regional Studies in Marine Science, 2025)

The Influence of Tidal Distortion on Extreme Water Levels in Casamance Estuary, Senegal - Amadou Diouf; Issa Sakho; Bamol Ali Sow; Julien Deloffre; Marcellin Samou Seujip; Mouhamadoul Bachir Diouf; Robert Lafite (Estuaries and Coasts, 2025)

Sea level rise and future shoreline changes along the sandy coast of Saloum Delta, Senegal - Issa Sakho; Mamadou Sadio; Ibrahima Camara; Mélinda Noblet; Aïchetou Seck; Cherdvong Saengsupavanich; Abdoulaye Ndour; Mouhamadoul Bachir Diouf (Arabian Journal of Geosciences, 2022)